Differentiation of sex chromosomes and karyotypic evolution in the eye-lid geckos (Squamata: Gekkota: Eublepharidae), a group with different modes of sex determination - Pokorná, Martina; Rábová, Marie; Ráb, Petr; Ferguson-Smith, Malcolm A; Rens, Willem; Kratochvíl, Lukáš (Chromosome research, 2010)
The eyelid geckos (family Eublepharidae) include both species with temperature-dependent sex determination and species where genotypic sex determination (GSD) was suggested based on the observation of equal sex ratios at several incubation temperatures. In this study, we present data on karyotypes and chromosomal characteristics in 12 species (Aeluroscalabotes felinus, Coleonyx brevis, Coleonyx elegans, Coleonyx variegatus, Eublepharis angramainyu, Eublepharis macularius, Goniurosaurus araneus, Goniurosaurus lichtenfelderi, Goniurosaurus luii, Goniurosaurus splendens, Hemitheconyx caudicinctus, and Holodactylus africanus) covering all genera of the family, and search for the presence of heteromorphic sex chromosomes. Phylogenetic mapping of chromosomal changes showed a long evolutionary stasis of karyotypes with all acrocentric chromosomes followed by numerous chromosomal rearrangements in the ancestors of two lineages. We have found heteromorphic sex chromosomes in only one species, which suggests that sex chromosomes in most GSD species of the eyelid geckos are not morphologically differentiated. The sexual difference in karyotype was detected only in C. elegans which has a multiple sex chromosome system (X(1)X(2)Y). The metacentric Y chromosome evolved most likely via centric fusion of two acrocentric chromosomes involving loss of interstitial telomeric sequences. We conclude that the eyelid geckos exhibit diversity in sex determination ranging from the absence of any sexual differences to heteromorphic sex chromosomes, which makes them an interesting system for exploring the evolutionary origin of sexually dimorphic genomes.
Keywords: Animals; fylogeneze; Sex Chromosomes; procesy určující pohlaví; ženské pohlaví; mužské pohlaví; pohlavní dimorfismus; Lizards; Sex Determination Processes; ještěři; Evolution, Molecular; druhová specificita; Karyotyping; Male; Species Specificity; molekulární evoluce; zvířata; Sex Characteristics; Phylogeny; pohlavní chromozomy; karyotypizace; Female